Current Updates on Diagnosis and Management of Cholangiocarcinoma: from Surgery to Targeted Therapy - Haryanto Surya; Murdani Abdullah; Erni Juwita Nelwan; Ari Fahrial Syam; Ignatius Bima Prasetya; Benedictus Stefanus; Cleopas Martin Rumende; Hamzah Shatri (Acta Medica Indonesiana)
Cholangiocarcinoma is commonly described as any malignancy arising from the lining of the bile duct and is recognized as one of the most common biliary malignancies. We conducted a literature review of current available evidences and guidelines. Based on the anatomical location of the origin of the mass, cholangiocarcinoma can be divided into intrahepatic, perihilar, and distal cholangiocarcinoma. Each of these subtypes has their own risk factors, best treatment options, and prognosis. The most common risk factors for cholangiocarcinoma also differs based on geography and population backgrounds. Histopathological biopsy remained the gold standard for cholangiocarcinoma diagnosis, however various advances has been made in diagnostic procedure, including MRCP, EUS, ERCP, EBUS, and cholangioscopy. Surgical resection is still the best treatment modality for cholangiocarcinoma, but it can only be done in few patients considering most patients were diagnosed in the unresectable state. Other treatment options includes conventional chemotherapy, locoregional therapy, systemic targeted therapy, and palliative best supportive care. Cholangiocarcinoma has an abundance of molecular targets and advances in biomolecular technologies bring further hope for future curative treatment options. Treatment options should be chosen individually based on each patient’s condition and setting. Cholangiocarcinoma is still a major health problem in hepatobiliary malignancies. Multiple options are available for cholangiocarcinoma treatments.